Racial Discrimination Reflected In Tate Taylor's The Help Movie (2011): A Sociological Approach - Khotimah, Nurindah Khusnul, Drs. Abdillah Nugroho, M.Hum, Titis Setyabudi, S.S., M.Hum (2013)
The major problem of this study is how the racial discrimination reflected in The Help movie (2011) by Tate Taylor. The objective of this study is to analyze the movie based on its structural elements and to analyze the movie based on the sociological analysis. In analyzing The Help, the writer uses qualitative method and Sociological approach. The data sources consist of primary data and secondary data sources. The primary data source is The Help movie and the secondary data sources are books or any information related to racial discrimination. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, based on the structural analysis of the movie, it shows that Taylor wants to express his idea about difference rule between white and black skin. Second, based on Sociological Approach, the conclusion is that there is racial discrimination in the Tate Taylor's The Help movie. Taylor shows that the racial discrimination is shown by the white women who become the employer of the black women who become the maid. The maids get many differences of the facilities from their employers.